Experimental investigation into fire resistance of HC‐FST columns under axial compression - Žygimantas Blaževičius; Audronis Kazimieras Kvedaras (Journal of Civil Engineering and Management, 2007)
A certain amount of analytical methods for determining fire resistance of concrete filled steel tubular columns are developed. Mostly those methods refer to or have as an origin the data about the results of real experiments. The research work on this kind of composite column behaviour under fire conditions with a wide range of different parameters measuring was performed. The behaviour of 16 axially loaded HC‐FST (hollow concrete filled steel tubular) columns without fire protection under conditions similar to ISO‐834 fire and under normal conditions was experimentally investigated and the results are presented in this paper. The experimental values of fire resistance were measured and the failure mode was determined for 4 axially loaded columns. And for the comparison of test parameters, 4 axially loaded HC‐FST columns were tested under normal conditions. In addition, 8 hollow concrete‐filled steel tubular stub columns and 4 hollow concrete tubular stub columns under normal conditions were tested. The final objective was to prepare experimental data for analysis and to find some analytical dependence between test parameters with the most significant influence on the fire results of HC‐FST columns.